2010
DOI: 10.1097/hjh.0b013e328338a075
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive effects of central angiotensin II infusion and restraint stress are reduced with age

Abstract: This study demonstrates that the role of central AngII diminishes with age in the regulation of BP both during baseline conditions and during stress, whereas the involvement of AngII in the regulation of HR remains unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…Consistent with previous studies [21,22,23], the present report demonstrates that BP increases significantly in old rats compared with that in the young, the pressor and tachycardic responses to stress and central AngII decreases with age, and adrenomedullar TH and DβH, and AT1 receptor mRNA expression increase with age, whereas hypothalamic TH decreases with age. Furthermore, hypothalamic Cu-ZnSOD and catalase levels decreased with age, and the increase in NADPH oxidase activity was associated with a corresponding increase in gp91 protein and p22 mRNA levels.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies [21,22,23], the present report demonstrates that BP increases significantly in old rats compared with that in the young, the pressor and tachycardic responses to stress and central AngII decreases with age, and adrenomedullar TH and DβH, and AT1 receptor mRNA expression increase with age, whereas hypothalamic TH decreases with age. Furthermore, hypothalamic Cu-ZnSOD and catalase levels decreased with age, and the increase in NADPH oxidase activity was associated with a corresponding increase in gp91 protein and p22 mRNA levels.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous studies, we demonstrated that the age-dependent increase in BP is accompanied by increases in adrenomedullary TH, DβH, and neuropeptide Y levels, which are all indicators of the sympathetic nervous system activity [21,22,23]. In addition, restraint stress and central AngII-induced BP and HR elevations were reduced with age.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An elevation in activity may also serve as a contributing mechanism for the negative energy balance. In this regard, a recent report considering the effect of aging on the hypertensive effects of Ang II noted that a similar dose of Ang II administered icv leads to elevated locomotor activity in both young and old rats (24).…”
Section: Discussionmentioning
confidence: 99%